Green Banking Initiatives: Study on the Nepalese Banking Sector - Khanal, Rajiv; Aryal, Om Prakash; Kandel, Sudarshan; Bashyal, Bhim Prasad (Crimson Journal of Science and Technology, 2025)
Introduction: This study aims to investigate green banking initiatives in Nepal’s commercial banks, emphasizing five major areas: green product development, green corporate social responsibility (CSR), green internal processes, green brand image, and green brand trust. The research seeks to understand how these factors contribute to sustainable finance within banks in a developing country context. Methods: The study uses a quantitative, cross-sectional approach. Data was gathered from 412 bank customers and employees in Makwanpur District. Analysis was performed using SmartPLS, evaluating the relationships between green banking constructs and the adoption of sustainable practices. Results: The findings of our study showed that all five factors significantly and positively affect green banking practices. Green product development and internal processes have the strongest impacts. The combined variables account for 61.5% of the variance in green banking adoption among Nepalese banks. Conclusions: For policy and managerial action, banks should prioritize innovative green products and eco-friendly internal operations. Policymakers are encouraged to strengthen regulations and promote awareness to support these initiatives. This research is original in its comprehensive perspective, integrating both customer and employee views in Nepal’s banking sector. Future research should expand geographically and use longitudinal methods.